Stressors and strains in combining work and family a study of Filipino working parents.[article]. - Alampay, MA. Regina H.
The study tapped 370 Filipino working parents in Metro Manila to determine between democratic, personality, family and work characteristics on total, work and no-work stressors and total, physiological, psychological and behavioral strains. Although the resulting hierarchical models are not robust, they do show significant relationships between particular demographic, personality, family and work-related variables and the various stressors and strains. Age, income, self-esteem, civil status, age of children, work level and dual -income households are the specific variables which predict one or more criterion outcomes. A significant interaction effect was also found between high-level work of both respondent and spouse. Human resource management implications are discussed and recommendations are forwarded with respect to organization policies and programs.